Integrative Epigenomic Analysis of Transcriptional Regulation of Human CircRNAs - Li, Xue-Cang; Tang, Zhi-Dong; Peng, Li; Li, Yan-Yu; Qian, Feng-Cui; Zhao, Jian-Mei; Ding, Ling-Wen; Du, Xiao-Juan; Li, Meng; Zhang, Jian; Bai, Xue-Feng; Zhu, Jiang; et al. (Frontiers in Genetics, 2021)
Circular RNAs (circRNAs) are evolutionarily conserved and abundant noncoding RNAs whose functions and regulatory mechanisms remain largely unknown. Here, we identify and characterize an epigenomically distinct group of circRNAs (TAH-circRNAs), which are transcribed to a higher level than their host genes. By integrative analysis of cistromic and transcriptomic data, we find that compared with other circRNAs, TAH-circRNAs are expressed more abundantly, have more transcription factors (TFs) binding sites and lower DNA methylation levels. Concordantly, TAH-circRNAs are enriched in open and active chromatin regions. Importantly, ChIA-PET results showed that 23%~52% of transcription start sites (TSSs) of TAH-circRNAs have direct interactions with cis-regulatory regions, strongly suggesting their independent transcriptional regulation from host genes. In addition, we characterize molecular features of super-enhancer-driven circRNAs in cancer biology. Together, this study comprehensively analyzes epigenomic characteristics of circRNAs, and identifies a distinct group of TAH-circRNAs which are independently transcribed via enhancers and super-enhancers by TFs. These findings substantially advance our understanding of the regulatory mechanism of circRNAs and may have important implications for future investigations of this class of noncoding RNAs.